2023
DOI: 10.1155/2023/8840427
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap: Exploring the Preclinical Potential of Pereskia grandifolia in Metabolic‐Associated Fatty Liver Disease

Edilson Rodrigues Albuquerque,
Gustavo Ratti da Silva,
Fernanda de Abreu Braga
et al.

Abstract: Metabolic-associated fatty liver disease (MAFLD) is a complex condition characterized by steatosis and metabolic disturbances. Risk factors such as diabetes, cigarette smoking, and dyslipidaemia contribute to its development and progression. Effective and safe therapies for MAFLD are urgently needed. Pereskia grandifolia has shown potential as an alternative treatment, but its effectiveness against liver disease remains unexplored. This research aims to determine the hepatoprotective properties of P. grandifol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The rats then received oral doses of the P. grandifolia extract (30, 100 and 300 mg/kg) or insulin in the final 2 weeks, in addition to simvastatin. The results demonstrated that the extracts reversed the increase in AST and ALT enzymes, as well as the changes in the lipid profile, oxidative stress, and liver damage caused by MAFLD [34].…”
Section: Animal Model Studiesmentioning
confidence: 91%
See 2 more Smart Citations
“…The rats then received oral doses of the P. grandifolia extract (30, 100 and 300 mg/kg) or insulin in the final 2 weeks, in addition to simvastatin. The results demonstrated that the extracts reversed the increase in AST and ALT enzymes, as well as the changes in the lipid profile, oxidative stress, and liver damage caused by MAFLD [34].…”
Section: Animal Model Studiesmentioning
confidence: 91%
“…These rats received extracts at doses of 30, 100, and 300 mg/kg for 3 weeks. It was reported that there were no significant changes in behavior, body weight, eating patterns, injuries, or abnormalities in organs including the liver and biochemical parameters in the blood, indicating that the plant did not cause immediate adverse effects in the rats [34]. Another study evaluated the acute toxicity of a dry ethanolic extract of Ora-pro-nobis (Pereskia aculeata), which was administered to female Wistar rats at doses of 1250 mg, 2500 mg, and 5000 mg/kg.…”
Section: Animal Model Studiesmentioning
confidence: 99%
See 1 more Smart Citation